2007
DOI: 10.1016/s1028-4559(08)60009-1
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Amnioinfusion for Oligohydramnios During the Early Second Trimester

Abstract: Amnioinfusion performed the first time might provide some benefits for those with early-onset oligohydramnios, such as to provide confirmation of rupture of membranes, detailed sonography examination and further counseling. We would recommend that this procedure be considered once for these cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…2 The infusion is evaded in the present cases. 8,9 In this study, no maternal and foetal complications were observed except only in one case (case no. 6) where a baby had a mild degree of Potter's facies, which consisted of compressed ears.…”
Section: Discussionmentioning
confidence: 48%
“…2 The infusion is evaded in the present cases. 8,9 In this study, no maternal and foetal complications were observed except only in one case (case no. 6) where a baby had a mild degree of Potter's facies, which consisted of compressed ears.…”
Section: Discussionmentioning
confidence: 48%
“…Eventually, 8 studies with data on 17 patients who underwent SAT for LUTO, CRA, or both were eligible. 1,2,[18][19][20][21][22][23] Eleven patients were from the United States, 3 were from Taiwan, and 1 each were from Canada, Germany, and the United Kingdom.…”
Section: Resultsmentioning
confidence: 99%
“…We used warm lactated Ringer's solution because its pH and electrolytes were most similar to levels previously measured in ovine amniotic fluid [21,22]. Human studies using saline have shown favorable results with amnioinfusions in alleviating fetal growth restriction and in diminishing pulmonary hypoplasia, neurologic injuries, and umbilical cord compression [3,14,23,24].…”
Section: Discussionmentioning
confidence: 98%